Standardized Hastasawanda Aesthetics in Dance Performing Arts - Maryono, Maryono; Suharti, Mamik; Sari, Cahyani Tunggal (Journal of Education Culture and Society, 2024)
Aim. This research is important because so far the existing aesthetic concept of traditional dance is no longer able to accommodate thinking about aesthetic concepts holistically. The aim of the standardisation study of performing arts aesthetics is to form a new aesthetic theory that meets standards based on the principles of aesthetic values that develop in the performing arts genre.Methods. This research article is based on qualitative research. The types of data and data sources and information were all obtained from the Hastasawanda aesthetic concept, dance aesthetic elements and Surakarta style dance performance documents. Data collection was carried out using library study and document study techniques. All data has been collected, classified, processed and analysed using the triangulation method.Results. This study found the standard Nawasapada aesthetic theory which consists of aspects: pralambang, paraga, movement, pepaes, wewandan, piece, stage, furniture and pannyandra.Conclusion. The novelty of Nawasapada's aesthetic theory is that it complements existing aesthetic aspects and becomes the basis for analytical tools in solving aesthetic phenomena in the performing arts in depth and openly. For this reason, it is hoped that this research will trigger future researchers to discuss it more sharply and in depth.